2020
DOI: 10.1111/mcn.13044
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants of anaemia in women of Nepal: a multilevel analysis

Abstract: In Nepal, the prevalence of anaemia decreased by 1% from 2006 to 2011 but increased by 6% from 2011 to 2016. In this study, we examined the changes in prevalence by possible factors from 2006 to 2016 along with the factors associated with anaemia among women of reproductive age (15–49 years) using the Nepal Demographic and Health Survey (NDHS) data from years 2006, 2011 and 2016. We used rate of change analysis to explore average annual rate of change (AARC) in anaemia prevalence and concentration curves and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…In this study, the prevalence of anaemia was found to be decreasing with increasing age. These findings are consistent with studies from Nepal, 36 Ethiopia, 39 Demographic Republic of Congo 73 and Benin. 60 The possible reason could be that the low fertility rates are high among older women.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the prevalence of anaemia was found to be decreasing with increasing age. These findings are consistent with studies from Nepal, 36 Ethiopia, 39 Demographic Republic of Congo 73 and Benin. 60 The possible reason could be that the low fertility rates are high among older women.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported by a previous study which was based on the analysis of the 2016 NDHS dataset. 36 The possible reason could be first, Nepal is an agrarian-based country and the staple diet may be similar for most of the households. 69 Second, it might be due to the nationwide open defecation free campaign initiated after 2011, which contributed to the reduction in hookworm infestation leading to decrease in anemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations